Analysis of User Acceptance and use of the GKI Salatiga+ Application using the UTAUT Model - Yohana Jenny Marisa; Evi Maria (Universitas Islam Indragiri, 2026)
The advancement of digital technology has encouraged religious institutions to adopt information systems to enhance services for their congregations; however, user acceptance is not always optimal. This study aims to analyze the factors influencing behavioral intention to use the GKI Salatiga+ application by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The study employs a quantitative explanatory approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through a questionnaire administered to 95 active users of the application. The results indicate that performance expectancy, effort expectancy, and facilitating conditions have a positive and significant effect on behavioral intention, with effort expectancy emerging as the most dominant factor. In contrast, social influence does not play a significant role in explaining the intention to use technology in this context. These findings suggest that, within a voluntary religious community context, the intention to use technology is more strongly influenced by perceived ease of use and system support than by social pressure. This study contributes by demonstrating that the relationships among constructs in the UTAUT model are context-dependent, particularly in community-based and voluntary technology adoption settings.